1992
DOI: 10.1139/b92-105
|View full text |Cite
|
Sign up to set email alerts
|

Amelioration of copper and nickel toxicity by iron plaque on roots of rice (Oryza sativa)

Abstract: Deposition of an iron oxide plaque or coating on roots of rice (Oryza sativa L. cv. M-201 84 Biggs) ameliorated the toxic effects of copper (Cu), nickel (Ni), and Cu + Ni on plant growth and affected patterns of metal uptake and accumulation. Plaque was formed on plants during 24 h in an anaerobic solution containing 20 mg ∙ L−1 iron at pH 5.5. Subsequently two additional coatings were deposited after new growth of roots. Plants were grown hydroponically in one-quarter strength Hoagland's solution and exposed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
69
2

Year Published

1997
1997
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(75 citation statements)
references
References 0 publications
4
69
2
Order By: Relevance
“…These results show some differences from those of Greipsson & Crowder (1992) and Greipsson (1994). Greipsson & Crowder (1992) grew rice {Oryza sativa) with and without plaque on roots in control, Cu, Ni, and Cu-I-Ni solutions for 34-70 d. Their results indicated that formation of plaque improved growth and ameliorated Cu and Ni toxicity under mildly toxic conditions of Cu and (or) Ni exposure. Greipsson (1994) also reported that plaque improved growth when rice seedlings were exposed to 0"5 fig ml^^ Cu solution.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…These results show some differences from those of Greipsson & Crowder (1992) and Greipsson (1994). Greipsson & Crowder (1992) grew rice {Oryza sativa) with and without plaque on roots in control, Cu, Ni, and Cu-I-Ni solutions for 34-70 d. Their results indicated that formation of plaque improved growth and ameliorated Cu and Ni toxicity under mildly toxic conditions of Cu and (or) Ni exposure. Greipsson (1994) also reported that plaque improved growth when rice seedlings were exposed to 0"5 fig ml^^ Cu solution.…”
Section: Discussionmentioning
confidence: 88%
“…Before the second and third exposure to Fe^"^, roots were placed in water for 4 h and then exposed to \S fig ml"^ Fe^"f or 48 h. Control plants were treated similarly but without Fe. The plants were subsequently placed directly into the solutions containing metals (Greipsson & Crowder, 1992). Growth was measured every 6 d (as the length of the longest leaf in each plant).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, no visible Fe toxicity symptoms were observed even though root dry weight decreased at Fe50 (Table 1), indicating that roots were more sensitive to the external Fe supply. In the literature, decreases (Ye et al 2001;Liu et al 2007) or increases (Greipsson and Crowder 1992;Greipsson 1994Greipsson , 1995 or no changes in root dry weight have been reported in response to pre-treatment to induce the formation of iron plaque on root surfaces. The distributions of P and Zn in different plant parts were in contrast with that of Cd (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Iron plaque therefore has chemical properties similar to those of iron oxides in the soil and can thus sequester both cations and anions and alter the uptake and accumulation of elements by plants. Iron plaque on rice root surfaces has been shown to sequester As (Liu et al 2004a,b andLiu et al 2005), Al (Chen et al 2006) and Se (Zhou et al 2007), alleviate toxicities of Cu, Ni and Zn to plants (Greipsson 1994(Greipsson , 1995Greipsson and Crowder 1992) and enhance Zn uptake when the amount of iron plaque was up to 12.1 g kg −1 root dry weight (Zhang et al 1998) and P uptake up to 24.5 g kg −1 root dry weight when Fe(OH) 3 was supplied to induce the formation of iron plaque (Zhang et al 1999). However, studies have also suggested that iron plaque is not the main barrier to Cd uptake by rice (Liu et al 2007).…”
Section: Introductionmentioning
confidence: 99%